PENERAPAN METODE LANGSUNG DALAM MENINGKATKAN KETERAMPILAN BERBICARA BAHASA ARAB - Fajrin, Ria Meri; Walfajri, Walfajri; Khotijah, Khotijah (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
Speaking skills are the main skills students must master in applying direct methods to learning Arabic. Learning Arabic Speaking Skills in class VII A MTsN 1 Lampung Timur in the 2019/2020 Academic Year, has not shown results that illustrate students' skills in actively speaking Arabic productive. The purpose of this research is to find out the improvement of students' Arabic speaking skills by applying the direct method. In this study the authors used (PTK) classroom action research with observation, documentary, and test data collection tools. The object of this study is students of class VII A. In this study researchers used the direct method. The results of the study stated that to improve their Arabic speaking skills students are equipped with basic skills in speaking that are very necessary when plunging into the field, such as the practice of applying dialogue patterns, vocabulary, rules, facial expressions, and so on.